Metabolomic profiling of urinary changes in mice with monosodium glutamate-induced obesity - Pelantová, Helena; Bártová, Simona; Anýž, Jiří; Holubová, Martina; Železná, Blanka; Maletínská, Lenka; Novák, Daniel; Lacinová, Zdena; Šulc, Miroslav; Haluzík, Martin; Kuzma, Marek (Analytical and bioanalytical chemistry, 2016)
Obesity with related complications represents a widespread health problem. The etiopathogenesis of obesity is often studied using numerous rodent models. The mouse model of monosodium glutamate (MSG)-induced obesity was exploited as a model of obesity combined with insulin resistance. The aim of this work was to characterize the metabolic status of MSG mice by NMR-based metabolomics in combination with relevant biochemical and hormonal parameters. NMR analysis of urine at 2, 6, and 9 months revealed altered metabolism of nicotinamide and polyamines, attenuated excretion of major urinary proteins, increased levels of phenylacetylglycine and allantoin, and decreased concentrations of methylamine in urine of MSG-treated mice. Altered levels of creatine, citrate, succinate, and acetate were observed at 2 months of age and approached the values of control mice with aging. The development of obesity and insulin resistance in 6-month-old MSG mice was also accompanied by decreased mRNA expressions of adiponectin, lipogenetic and lipolytic enzymes and peroxisome proliferator-activated receptor-gamma in fat while mRNA expressions of lipogenetic enzymes in the liver were enhanced. At the age of 9 months, biochemical parameters of MSG mice were normalized to the values of the controls. This fact pointed to a limited predictive value of biochemical data up to age of 6 months as NMR metabolomics confirmed altered urine metabolic composition even at 9 months.
Keywords: Insulin; glutamát sodný; Peroxisome Proliferator-Activated Receptors; Male; inzulin; Obesity; Metabolomics; Diabetes; metabolomika; receptory aktivované proliferátory peroxizomů; krevní glukóza; Monosodium glutamate (MSG) induced obesity; obezita; Sodium Glutamate; mužské pohlaví; NMR; metabolismus lipidů; Mouse model; moč; Animals; lidé; játra; Urine; Humans; zvířata; Lipid Metabolism; myši; Liver; Mice; Blood Glucose